Peningkatan Pertumbuhan dan Hasil Kacang Merah (Phaseolus Vulgaris L) melalui Aplikasi Pupuk Organik Cair Berbasis Sumber Daya Lokal - Bina Karo; Fatiani Manik; Darkam Musaddad (Universitas Quality, 2021)
Red beans (Phaseolus vulgaris L.) or jogo beans are in great demand by the public, because of their good nutritional value and can be made in various dishes. Low-cost agriculture can be carried out through an environmentally friendly agricultural system by utilizing local natural materials around the location such as kipait, rabbit manure, fish fertilizer, vegetable and fruit waste without reducing the quality and quantity of vegetables. This study aims to determine the increase in growth and yield of kidney beans (Phaseolus Vulgaris L) through the application of Liquid Organic Fertilizer (LOF) based on local resources. This research was conducted in the IP2TP Berastagi garden, Karo Regency, with an altitude of ± 1340 meters above sea level, andisol soil types. This research was carried out from May to September 2020. The design used in this study was a Randomized Block Design (RBD) with 3 replications and 10 treatments, namely: A=Without LOF (Control), B=Kotciplus LOF, 10 ml / l water, C=LOF Kotciplus, 20 ml / l water, D=LOF Kotciplus, 30 ml / l water, E=LOF Kipait, 10 ml / l water, F=LOF Kipait, 20 ml / l water, G=LOFKipait , 30 ml / l water, H=LOF Market Waste, 10 ml / l water, I=LOF Market Waste, 20 ml / l water, J=LOF Market Waste, 30 ml / l water. The results showed that the application of several types and concentrations of POC on kidney beans did not have a significant effect on growth or yield. However, there was a tendency that in general the plants treated with POC showed a higher yield compared to the yields of plants that were not given POC. Likewise, for each type of POC the higher the concentration the higher the yield.